2012
DOI: 10.3923/pjbs.2012.277.283
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by Hibiscus rosa-sinensis: Effect on the Humoral and Cellular Immune Response of Mus Musculus

Abstract: In West India, the Hibiscus rosa-sinensis L. (Malvaceae) is traditionally used as tea as a natural diuretic. Extract of this plant contains Vitamin C and is used traditionally as a mild medicine. In spite of a long history of traditional medicinal value of H. rosa-sinensis still no data are available for immunomodulatory activity. In present investigation, aqueous extract of H. rosa-sinensis (AEHrs) (500 mg kg(-1) BW) was intraperitoneally (IP) injected to the male Swiss albino mice (Mus musculus) to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…For example, recent studies found that Hibiscus polyphenols inhibit melanoma cell growth and viability 10 . However, while H. rosa-sinensis flowers are commonly used to make medicinal tea,11, 12 these previous studies were performed with organic solvent extracts of leaves from different strains, namely Hibiscus sabdariffa 10 …”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies found that Hibiscus polyphenols inhibit melanoma cell growth and viability 10 . However, while H. rosa-sinensis flowers are commonly used to make medicinal tea,11, 12 these previous studies were performed with organic solvent extracts of leaves from different strains, namely Hibiscus sabdariffa 10 …”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory and antioxidant properties of H. sabdariffa flower play an important role in immunomodulatory activity (Fakeye, 2008;Mishra et al, 2012). The intensity of the inflammatory response is controlled by the recruitment of inflammatory cells into the inflammatory lesion (Zhang and An, 2007).…”
Section: Anthocyanin-foxp3mentioning
confidence: 99%
“…Hibiscus rosa-sinensis L. atau bunga sepatu merupakan tanaman yang memiliki khasiat empiris, sebagai obat keputihan, dan diuretik alami. Hibiscus rosa-sinensis L. mengandung senyawa alkaloid, flavonoid, polifenol, dan asam amino [17], [35], [36].…”
Section: Hibiscus Rosa-sinensis Lunclassified
“…Senyawa yang berperan dalam respon imun terhadap hewan uji yaitu flavonoid. Flavonoid mampu meningkatkan titer antibodi secara signifikan serta meningkatkan respon humoral, dengan cara merangsang subset makrofag dan B-limfosit yang berperan dalam sintesis antibodi [17].…”
Section: Hibiscus Rosa-sinensis Lunclassified